Byssus of green-lipped mussel Perna viridis as a biomonitoring biopolymer for zinc pollution in coastal waters - Yap, Chee Kong; Al-Mutairi, Khalid Awadh (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The present study aimed to confirm the use of the byssus (BYS) of the green-lipped mussel Perna viridis as a biomonitoring biopolymer for zinc (Zn) by comparing it to copper (Cu) and cadmium (Cd) pollution in coastal waters under experimental field conditions, based on the transplantation of caged mussels between polluted and unpolluted sites in the Straits of Johore (SOJ). Four important evidential points were found in the present study. First, the 34 field-collected populations with BYS/total soft tissue (TST) ratios > 1 indicated that the BYS was a more sensitive, concentrative, and accumulative biopolymer for the three metals than TST. Significant (p < 0.05) and positive correlations between BYS and TST in terms of the levels of the three metals were observed. Second, the data obtained in the present study were well-supported by the interspecific comparison, which indicated that the BYS of P. viridis was a significantly better biomonitoring biopolymer for the identification of coastal areas exposed to Zn, Cd, and Cu pollution and played the role of an excretion route of metal wastes. Third, the higher positive correlation coefficients for the metals between the BYS sedimentary geochemical fractions than the TST sedimentary geochemical fractions indicated that the BYS was more reflective of metal bioavailability and contamination in coastal waters. Fourth, and most importantly, the field-based cage transplantation study clearly indicated the accumulation and elimination of the three metals by the BYS in both polluted and unpolluted sites in the Straits of Johore. In sum, the BYS of P. viridis was confirmed as a better biopolymer than TST for Zn, as well as Cd and Cu, bioavailability and contamination in tropical coastal waters.